Bioremediation of hydrocarbon-contamidated Soils - Muyibi, Suleyman Aremu; Al-Khatib, Ma'an Fahmi Rashid; Alam, Md. Zahangir; Kabbashi, Nassereldeen Ahmed ([s.n], 2012)
Crude oil spills resulting from the leakage from underground storage tanks, pipelines and other industrial operations are an important source of soil contamination. Bioremediation is an emerging technology that is used to recover contaminated soils. Laboratory scale experiments were carried out to bioremediate crude oil contaminated soil (COCS) using isolated bacterial consortium and domestic waste water sludge as nutrient source. The bacterial strains were isolated from COCS by enrichment culture using minimal salt medium (MSM) with crude oil as sole carbon source. The isolated strains were purified and monitored for their growth by monitoring the optical density (OD600). Four bacterial consortiums were formed and monitored for their growth on MSM with crude oil as sole carbon source. The fastest growing consortium (IMN201) was selected for the kinetics study and the biodegradability test in soil slurry. The bioremediation experiments were designed using DesignExpert 6.0.8 software by optimizing the amount of crude oil, microbial inoculum and sludge which are initially added to the autoclaved soil. Fifteen runs were carried out until no more microbial activity was noticed. The biodegradability test showed 95.8% removal of TPH within 7 days of incubation while the kinetics parameters were µmax = 0.02 hr1 and ks = 2.2% v/v oil. From the bioremediation results, the optimum degradation obtained was 99.3% within 13 days.